Analisis Faktor-Faktor Yang Mempengaruhi Turnover Intention Karyawan Pada PT. Bankaltimtara Di Tenggarong - Rahmawati, Nisvi Putri; Syahruddin.s, Syahruddin.S; Idham, Idham (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2020)
Abstract: Starting from 2010 to 2017, employees of PT. BANKALTIMTARA Tenggarong that left reached the lowest number of 3.24% and the highest was 12.65% of the total employees. The average employee turnover rate in the last 3 (three) years at PT. BANKALTIMTARA Tenggarong has exceeded the tolerable standard. From the ANOVA test or F test, it is obtained that the F count is 43.018, while the F table value is 2.56, this means that all the independent variable was able to show a significant effect on employee turnover intention at PT. BANKALTIMTARA in Tenggarong. The number R is shows that the correlation between job satisfaction, job stress and organizational commitment to employee turnover intention is a strong relationship. Partially, Job stress, organizational commitment, and job satisfaction have a positive and significant effect on employee turnover intention at PT. BANKALTIMTARA in Tenggarong. Based on the comparison of partial correlation values ​​on the correlation table, it shows that the organizational commitment variable has the most dominant influence on employee turnover intention at PT. BANKALTIMTARA in Tenggarong So that the company must be able to maintain the work commitment of its employees. Keywords: Job Satisfaction, Stress, Organizational Commitment, Turnover Intention